Techniques for Amelioration of Trace Metal Contaminated Soils - Amrit Kumar Jha; Kaushik Chatterjee; Birendra Kumar Mehta (Recent Progress in Plant and Soil Research Vol. 1, 2021)
Trace metals are ubiquitous in the environment and present in small amounts in normal condition. Typically, the principal reservoir of trace elements is the geological substrate followed by the oceans, soil, biota and atmosphere. Contamination of trace metals refers to their anthropogenic accumulation, which may or may not inflict any harm to the system or organism. Soil is the key component of natural ecosystems as environmental sustainability depends largely on a sustainable ecosystem. Unlike other environmental components, pollutants have long residence time in soil. Therefore, soil acts as a sink or a filter in which pollutants are accumulated rapidly but depleted slowly. Effective monitoring of the heavy metal builds up requires knowledge of threshold limits of toxicity of these metals in soils, plants and animals including human beings. These toxicity limits serve a dual purpose of maintaining both soil and crop productivity by planning metal loading rates in such a way that phyto-/zoo-toxic limits of the metals are not exceeded. Soil remediation is the return of soil to a condition of ecological stability together with the establishment of plant communities it supports or supported to condition prior to disturbance. Plant based bioremediation technologies have been collectively termed as phytoremediation, refers to the use of green plants and their associated micro biota for the in-situ treatment of contaminated soil. Plants have three basic strategies for growth on metal contaminated soil and on this basis, they are grouped as metal excluders, metal indicators and metal hyper accumulators. The plant growth promoting rhizobacteria increase heavy metal sequestration capacity of plants by recycling nutrients, maintaining soil structure, detoxifying chemicals and controlling pests, while decreasing toxicity of heavy metals by changing their bioavailability. Arbuscular mycorrhizal fungi are soil microorganisms that establish mutual symbiosis with the majority of higher plants, providing a direct physical link between soil and plant roots. The fungi can accelerate the revegetation of severely degraded lands such as coal mines or waste sites containing high levels of heavy metals. Contaminated soils have classically been ameliorated using amendments such as lime, phosphate and organic matter. The addition of lime generally reduces the bioavailability of heavy metals.